Implementasi Metode Bermain dalam Menstimulasi Kemampuan Kognitif dan Sosial Anak Usia Dini - Masdiana Maula; Rukiah; Rukiyah, Ity (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to describe the implementation of play methods in stimulating the cognitive and social abilities of young children. The research was conducted using a descriptive qualitative approach. The research subjects consisted of 17 Buah Hati Kindergarten children aged 5-6 years, who were selected using a purposive sampling technique based on the children's involvement in play activities designed by the teacher. Data was collected through observation, interviews and documentation, then analyzed using the Miles, Huberman and Saldana model including data collection, data condensation, data presentation and conclusion drawing, with triangulation validation techniques and sources. The results of the research show that play activities that are applied systematically, such as playing with blocks, stick men, making weapons from banana stems, and matching pictures of flags, make a significant contribution to children's development. Block games train logic, creativity and problem-solving skills. Stick man games hone creativity and critical thinking skills through discussion and collaboration. The activity of making weapons from banana stems fosters imagination, gross motor coordination and cooperation, while the flag matching game improves memory, symbol recognition and social interaction. The conclusion of this research confirms that play methods, if well designed and relevant, can be an effective learning strategy in supporting the cognitive and social development of early childhood.